2021
DOI: 10.26434/chemrxiv.14229134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Phase Transition on the Thermal Transport in Isoreticular DUT Materials

Abstract: <p></p><p>Soft porous crystals (SPCs) can undergo large-amplitude phase transitions under external stimulus such as mechanical pressure, gas adsorption, and temperature while retaining their structural integrity. During the gas adsorption process, the generated latent heat is needed to be effectively removed. Thus, understanding the effect of phase transition on the thermal transport in SPCs becomes extremely important for their applications in storage and separation applications. </p> … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The single-crystal-to-single-crystal (SCSC) conversion is an intriguing and essential process in chemistry and material science and is an important feature in the preparation of coordination polymers [132][133][134][135][136][137][138][139] . Over the last few decades, much research demonstrated that SCSC conversions of MOFs could be triggered by external stimuli, including physical and chemical processes, such as temperature, pressure, gas adsorption, etc.…”
Section: Phase Transition Methodsmentioning
confidence: 99%
“…The single-crystal-to-single-crystal (SCSC) conversion is an intriguing and essential process in chemistry and material science and is an important feature in the preparation of coordination polymers [132][133][134][135][136][137][138][139] . Over the last few decades, much research demonstrated that SCSC conversions of MOFs could be triggered by external stimuli, including physical and chemical processes, such as temperature, pressure, gas adsorption, etc.…”
Section: Phase Transition Methodsmentioning
confidence: 99%